A proposal to risk their friendship - Allen, Louise, 1949- (Allen, Louise, 1949- Liberated ladies., 2021)
"Respecting each other's desire for independence, Lord Henry Cary and writer Melissa Taverner enjoy an uncomplicated friendship. Henry finds her amusing, intelligent company, but she's also an attractive woman, and he's alarmed to find lust sneaking in... Having always viewed marriage as a cold matter of convenience, Henry dare not risk their friendship with a proposal. Yet when their closeness sparks rumors, he might not have a choice!"--